Quantitative pupillometry and radiographic markers of intracranial midline shift: A pilot study - Kim, Ivy So Yeon; Balogun, Oluwafemi O.; Prescott, Brenton R.; Saglam, Hanife; Olson, DaiWai M.; Speir, Kinley; Stutzman, Sonja E.; Schneider, Nathan; Aguilera, Veronica; Lussier, Bethany L.; Smirnakis, Stelios M.; Dupuis, Josée; et al. (Frontiers in Neurology, 2022)
Background: Asymmetric pupil reactivity or size can be early clinical indicators of midbrain compression due supratentorial ischemic stroke or primary intraparenchymal hemorrhage (IPH). Radiographic midline shift is associated with worse functional outcomes and life-saving interventions. Better understanding of quantitative pupil characteristics would be a noninvasive, safe, and cost-effective way to improve identification of life-threatening mass effect and resource utilization of emergent radiographic imaging. We aimed to better characterize the association between midline shift at various anatomic levels and quantitative pupil characteristics. Methods: We conducted a multicenter retrospective study of brain CT images within 75 minutes of a quantitative pupil observation from patients admitted to Neuro-ICUs between 2016 and 2020 with large (>1/3 of the middle cerebral artery territory) acute supratentorial ischemic stroke or primary IPH>30mm3. For each image, we measured midline shift at the septum pellucidum (MLS-SP), pineal gland shift (PGS), the ratio of the ipsilateral to contralateral midbrain width (IMW/CMW), and other exploratory markers of radiographic shift/compression. Pupil reactivity was measured using an automated infrared pupillometer (NeurOptics®,Inc.), specifically the proprietary algorithm for Neurological Pupil Index® (NPi). We used rank-normalization and linear mixed-effects models, stratified by diagnosis and hemorrhagic conversion, to test associations of radiographic markers of shift and asymmetric pupil reactivity (Diff NPi), adjusting for age, lesion volume, Glasgow Coma Scale, and osmotic medications. Results: Of 53 patients with 74 CT images, 26 (49.1%) were female, and median age was 67 years. MLS-SP and PGS were greater in patients with IPH, compared to patients with ischemic stroke (6.2 v. 4.0mm, 5.6 v. 3.4mm, respectively). We found no significant associations between pupil reactivity and the radiographic markers of shift when adjusting for confounders. However, we found potentially relevant relationships between MLS-SP and Diff NPi in our IPH cohort (β=0.11,SE 0.04,P=0.01), and PGS and Diff NPi in the ischemic stroke cohort (β=0.16,SE 0.09,P=0.07). Conclusion: We found the relationship between midline shift and asymmetric pupil reactivity may differ between IPH and ischemic stroke. Our study may serve as necessary preliminary data to guide further prospective investigation into how clinical manifestations of radiographic midline shift differ by diagnosis and proximity to the midbrain.